2018
DOI: 10.1021/acs.jafc.8b03763
|View full text |Cite
|
Sign up to set email alerts
|

Absorption, Metabolism, and Pharmacokinetics Profiles of Norathyriol, an Aglycone of Mangiferin, in Rats by HPLC-MS/MS

Abstract: Norathyriol, an aglycone of mangiferin, is a bioactive tetrahydroxyxanthone present in mangosteen and many medicinal plants. However, the biological fate of norathyriol in vivo remains unclear. In this study, the absorption and metabolism of norathyriol in rats were evaluated through HPLC-MS/MS. Results showed that norathyriol was well absorbed, as indicated by its absolute bioavailability of 30.4%. Besides, a total of 21 metabolites of norathyriol were identified in rats, including methylated, glucuronidated,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 36 publications
(52 reference statements)
1
6
0
Order By: Relevance
“…Mangiferin can also be excreted directly through phase II reaction. Besides, the study has shown that glucuronidation and sulfation conjugates were found to be the main forms existing in vivo after administration, which is consistent with our experimental results . Norathyriol, the deglycosylation metabolite of mangiferin was responsible for the hypouricaemic effect of mangiferin via inhibiting xanthine oxidase activity .…”
Section: Discussionsupporting
confidence: 90%
“…Mangiferin can also be excreted directly through phase II reaction. Besides, the study has shown that glucuronidation and sulfation conjugates were found to be the main forms existing in vivo after administration, which is consistent with our experimental results . Norathyriol, the deglycosylation metabolite of mangiferin was responsible for the hypouricaemic effect of mangiferin via inhibiting xanthine oxidase activity .…”
Section: Discussionsupporting
confidence: 90%
“…Compound M27 with the retention time at 26.42 min, exhibited deprotonated molecular ion at m/z 401.1240, 48 Da more than that of compound 41 , revealing that they were three hydroxyls bonding metabolites . Compound M28 with the retention times at 40.98 min, exhibited [M‐H] − at m/z 433.0950, 80 Da more than that of compound P29 , revealing that they were sulfate conjugation metabolites . The most abundant signal in secondary fragmentation map was at m/z 353.1383, which implied the neutral loss of 80 Da (SO 3 ) from the parent ion, attesting the compound was readily associated with sulfate conjugation.…”
Section: Resultsmentioning
confidence: 99%
“…Sugar compounds rhamnose, glucose, and sucrose were detected at m/z 163.0598, 179.0547, and 341.1077, respectively [14,15]. (Figure S8) [31]. m/z 285.0615, 321.0604, and 331.0655 were proposed to be hydroquinone glucuronide, leucodelphinidin, and 3-Glucogallic acid following the comparison with the HMDB database and literatures [15,32].…”
Section: Identification Of Secondary Metabolitesmentioning
confidence: 94%
“…The peak at m/z 191.0548 [M-H] − was supposed as quinic acid by detecting fragmented peaks at m/z 173.0445, 127.0388, 109.0282, and 93.0333 with the loss of H 2 O, CH 4 O 3 , CH 6 O 4 , and CH 6 O 5 , accordingly (Figure S7) [30]. m/z 259.0242 [M-H] − was identified as norathyriol based on fragmentation peaks at m/z 231.0295, 215.0345, 187.0394, and 171.0444 with the loss of CO, CO 2 , C 2 O 3 , and C 2 O 4 (FigureS8)[31]. m/z 285.0615, 321.0604, and 331.0655 were proposed to be hydroquinone glucuronide, leucodelphinidin, and 3-Glucogallic acid following the comparison with the HMDB database and literatures[15,32].m/z 337.0917 showed fragmented ions at m/z 191.0555, 173.0449, and 163.0393 upon fragmentation at collision energy (CE) 10 eV and it was characterized as 3-p-Coumaroylquinic acid[20,33].…”
mentioning
confidence: 99%